DISSOLVED ORGANIC CARBON IN RIDGE-AXIS AND RIDGE-FLANK HYDROTHERMAL SYSTEMS - Lang S.Q.; Butterfield D.A.; Lilley M.D.; Paul Johnson H.; Hedges J.I. (My University, 2006)
The circulation of hydrothermal fluid through the upper oceanic crustal reservoir has a large impact on the chemistry of seawater, yet the impact on dissolved organic carbon (DOC) in the ocean has received almost no attention. To determine whether hydrothermal circulation is a source or a sink for DOC in the oceans, we measured DOC concentrations in hydrothermal fluids from several environments. Hydrothermal fluids were collected from high-temperature vents and diffuse, low-temperature vents on the basalt-hosted Juan de Fuca Ridge axis and also from low-temperature vents on the sedimented eastern flanks. High-temperature fluids from Main Endeavour Field (MEF) and Axial Volcano (AV) contain very low DOC concentrations (average = 15 and 17 ?M, respectively) compared to background seawater (36 ?M). At MEF and AV, average DOC concentrations in diffuse fluids (47 and 48 ?M, respectively) were elevated over background seawater, and high DOC is correlated with high microbial cell counts in diffuse fluids. Fluids from off-axis hydrothermal systems located on 3.5-Ma-old crust at Baby Bare Seamount and Ocean Drilling Program (ODP) Hole 1026B had average DOC concentrations of 11 and 13 ?M, respectively, and lowered DOC was correlated with low cell counts. The relative importance of heterotrophic uptake, abiotic sorption to mineral surfaces, thermal decomposition, and microbial production in fixing the DOC concentration in vent fluids remains uncertain. We calculated the potential effect of hydrothermal circulation on the deep-sea DOC cycle using our concentration data and published water flux estimates. Maximum calculated fluxes of DOC are minor compared to most oceanic DOC source and sink terms. ? 2006 Elsevier Inc. All rights reserved.
Keywords: DISSOLVED ORGANIC CARBON; FLUID COMPOSITION; HYDROCHEMISTRY; HYDROTHERMAL FLUID